3D extraoral morphometric changes after implant surgery: an exploratory pilot study using stereophotogrammetry - Ercal, Pinar; Calciolari, Elena; Patel, Rajvi; Zou, Lifong; Mardas, Nikolaos; Donos, Nikolaos (Quintessence Publishing Co Inc, 2024)
Objective: This pilot study aimed to evaluate, for the first time, the changes in facial tissues following the placement of a single dental implant. Method and materials: Patients were scanned with a 3D facial scanner (3dMD) before implant surgery, immediately after surgery (T1), at 7days postoperatively (T2), and at the impression stage (T3). Acquired images were processed using the 3dMDvultus (3dMD) software program and volume differences and linear depth measurements were calculated to determine the morphometric changes over time. A total of 11 patients were included in the analyses. Descriptive statistics were employed to analyze the data. Results: The volumetric changes and maximum depth differences indicated an initial increase, followed by a progressive decrease in tissue volume after implant placement in the area of the surgery. The volume change values ranged between 2.5 and 3.9 cm 3 for Tl, whereas for T2, the volume change decreased to a range of 0.8 to 1.8cm 3 . Maximum depth differences ranged between 2.06 and 2.80 mm in the soft tissues immediately after the implant surgery and reduced to around 2.01 to 0.55 mm at the impression stage. The amount of painkiller used was not related to the magnitude of linear depth measurements at any assessed time point. Conclusion: There was a longitudinal decrease in soft tissue volume and depth difference in extraoral soft tissues in the region of implant placement after surgery up to 6weeks. The use of a facial scanner is a promising noninvasive method to monitor 3D morphometric changes after implant surgery.
Keywords: dental implants; facial scan; stereophotogrammetry